Quantum Mechanical Engine for the Quantum Rabi Model - Retamal-Abarzua, J; Alvarado-Barrios, G; Albarran-Arriagada, F (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
We consider a purely mechanical quantum cycle comprised of adiabatic and isoenergetic processes. In the latter, the system interacts with an energy bath keeping constant the expectation value of the Hamiltonian. In this work, we study the performance of the quantum cycle for a system described by the quantum Rabi model for the case of controlling the coupling strength parameter, the resonator frequency, and the two-level system frequency. For the cases of controlling either the coupling strength parameter or the resonator frequency, we find that it is possible to closely approach to maximal unit efficiency when the parameter is sufficiently increased in the first adiabatic stage. In addition, for the first two cases the maximal work extracted is obtained at parameter values corresponding to high efficiency, which constitutes an improvement over current proposals of this cycle.